Nontrivial Solution for a Nonlocal Elliptic Transmission Problem in Variable Exponent Sobolev Spaces - Bilal Cekic; Rabil A. Mashiyev (Abstract and Applied Analysis)
In this paper, by means of adequate variational techniques and the theory of the variable exponent Sobolev spaces, we show the existence of nontrivial solution for a transmission problem given by a system of two nonlinear elliptic equations of p(x)-Kirchhoff type with nonstandard growth condition.